2003
DOI: 10.1159/000070394
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Risk Factors for Development of Duodenal Ulcer in Helicobacter pylori-Infected Patients

Abstract: Background: Although Helicobacter pylori is a significant etiologic factor of peptic ulcer disease, it remains unknown why ulcers develop only in the minority of infected individuals. Aim: The aim of this cross-sectional study was to evaluate the association between the presence of duodenal ulcer in H. pylori-infected patients and different risk factors. Methods: A total of 122 H. pylori-infected patients were enrolled; 79 had duodenal ulcer and 43 gastritis. Univariate analysis was conducted using either Fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
2
5
0
1
Order By: Relevance
“…Our results suggest a strong correlation between smoking status and peptic ulcer frequency as previously shown by other authors (Chen et al 1999;Konturek et al 2003;Moshkowitz et al 2000;Regula et al 2003).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results suggest a strong correlation between smoking status and peptic ulcer frequency as previously shown by other authors (Chen et al 1999;Konturek et al 2003;Moshkowitz et al 2000;Regula et al 2003).…”
Section: Discussionsupporting
confidence: 91%
“…Schilling et al (2000) concluded that Hp infection status does not allow distinguishing ulcer or nonulcer dyspepsia patients from asymptomatic seropositives. In fact, only 10-20% of Hp colonizations result in duodenal or gastric ulcer disease because increased acidity is not mandatory in Hp-induced gastritis (Fennerty 2005;Marshall 2003;Kist and Glockner 2003;Regula et al 2003). From the present results, it is more likely that a disruption of the circadian periodic as result of chronic shift work is not a risk factor for a duodenal or gastric ulcer disease such as stress or smoking (Johns et al 2005;Jones 2006;Levenstein 2002;Regula et al 2003).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…No processo de ulcerogênese, as pesquisas apontam para as cepas ulcerogênicas 22 associadas a características próprias do hospedeiro, as quais não foram objetos deste estudo.…”
Section: Discussionunclassified
“…However, in this study, the combination of colonization by H. pylori and NSAID use appeared to prevent the appearance of duodenal ulcer. In another study of 122 infected patients, multivariate analysis of host, strain and environmental factors did not identify any single factor or combination of factors that could differentiate unequivocally patients with duodenal ulcer compared to gastritis 17 . In humans, a long‐term study of asymptomatic blood donors who were colonized by H. pylori confirms that with time, a proportion go on to develop ulcer disease 18 .…”
Section: Environmental Risksmentioning
confidence: 99%